Tissue characterization of local myocardium using phase frequency spectrum of ultrasonic RF signal - Ishii, Hirotake; Tsuruoka, Shinji; Ibrahimy, Muhammad Ibn; Kimura, Fumitaka; Wakabayashi, Tetsushi; Ohyama, Wataru; Sekioka, Kiyotsugu (2003)
A new phase frequency spectrum (PFS) method is proposed to estimate regional myocardial tissue character and function during cardiac cycle. The analysis employs the small range centering on the point tracked by the tracking system of a RF signal, and applies time-frequency analysis (wavelet transform) to the envelope of the RF signal. Result of the analysis is shown as two-dimensional image between frequency spectrum and cardiac-phase. The change of the phase frequency spectrum is measured and the diagnostic usefulness of the analysis for a lot of normal and abnormal hearts is confirmed experimentally.